PERLINDUNGAN KONSUMEN DALAM TRANSAKSI E-COMMERCE: SUATU PERSPEKTIF HUKUM ISLAM - Elisa Siti Widyastuti; Tiya Rissa Kamila; Panji Adam Agus Saputra (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
A trade activity through internet media is called electronic commerce (e-commerce).  Consumers who transact through the internet tend to cause losses caused by business actors.  The e-commerce transaction process starts from promotional and marketing issues to selling, payment and contract making issues.  The purpose of this study is to examine the law of protection for consumers in e-commerce transactions according to the Islamic view. The research method used in this study is a qualitative method with the data collection technique used is a literature study, namely a literature study with data sources from several book references and internet media related to the specific problems of this study. The results of this study show that business transactions through e-commerce are a new alternative in doing business in today's era.  The transaction process through e-commerce according to Islam is declared valid if aspects of consumer protection can be guaranteed and proven in accordance with the rules that have been determined by the syara' and as long as they are not prohibited by sharia or contrary to the postulates. REFERENCES Abdullah, J. (2015). Analisis Asas Konsesualisme Di Lembaga Keuangan Syariah. Jurnal Iqtishaida, 281-304. Azizah. (2019). LEGALITAS TANDA TANGAN ELEKTRONIK PEJABAT DALAM RANGKA MENDUKUNG E-GOVERNMENT. Retrieved from Mahkamah Agung Republik Indonesia: https://www.mahkamahagung.go.id/id/artikel/3737/legalitas-tanda-tangan-elektronik-pejabat-dalam-rangka-mendukung-e-government Azwar, T. P. (2014). MENGENAL PERJANJIAN DAN KONTRAK. Retrieved from Agam: https://www.agamkab.go.id/Agamkab/detailkarya/533/mengenal-perjanjian-dan-kontrak.html Chintya, A. (2020). Keabsahan Pembuktian Elektronik dalam Persidangan Perdata di Pengadilan Agama. Retrieved from https://pa-kotabumi.go.id/hubungi-kami/artikel-makalah/1037-keabsahan-pembuktian-elektronik-dalam-persidangan-perdata-di-pengadilan-agama.html Kastanoli. (2022). Surat An Nisa Ayat 59: Latin, Arti, Makna tentang Perintah Taat kepada Allah dan Ulil Amri. Retrieved from iNews: https://www.inews.id/lifestyle/muslim/surat-an-nisa-ayat-59-latin-arti-makna Online, T. H. (2022). Asas Perlindungan Konsumen dan Tujuan Perlindungannya. Retrieved from Hukum Online.Com : https://www.hukumonline.com/berita/a/asas-perlindungan-konsumen-dan-tujuannya-lt623bc8fd4931f Pratama, B. (2017). MENGENAL KONTRAK ELEKTRONIK, CLICK-WRAP AGREEMENT DAN TANDA TANGAN ELEKTRONIK. Retrieved from Bussiner University Bussiner Law: https://business-law.binus.ac.id/2017/03/31/mengenal-kontrak-elektronik-click-wrap-agreement-dan-tanda-tangan-elektronik/ R, F. A. (2022). Pengertian Khiyar, Etika Transaksi Jual Beli yang Diatur dalam Islam. Retrieved from Parenting Islam1: https://www.orami.co.id/magazine/khiyar RI, D. (2012). UU Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik. Retrieved from Referensi HAM : https://referensi.elsam.or.id/2015/02/uu-nomor-11-tahun-2008-tentang-informasi-dan-transaksi-elektronik/ Rie. (2014). E-Commerce. Retrieved from Bppitk: https://bpptik.kominfo.go.id/2014/12/19/645/e-commerce/ Tunardy, W. T. (2012). Jenis-Jenis Perjanjian. Retrieved from Jurnal Hukum: https://www.jurnalhukum.com/jenis-jenis-perjanjian/ Umum, P. (2020). Mengenal Maqashid Syariah, Pengertian dan Bentuk-Bentuknya. Retrieved from Ponpes Al-Hasanah Bengkulu: https://ponpes.alhasanah.sch.id/pengetahuan/mengenal-maqashid-syariah-pengertian-dan-bentuk-bentuknya/